Experimental Nanovaccine Offers Protection Against Repeat Exposures to Trypanosoma cruzi Through Activation of Polyfunctional T Cell Response - Chowdhury, Imran H.; Lokugamage, Nandadeva; Garg, Nisha Jain (Frontiers in Immunology, 2020)
A parasitic protozoan Trypanosoma cruzi (T. cruzi) is the etiologic agent of Chagas disease. Previously, we have identified T. cruzi antigens TcG2 and TcG4 as potential vaccine candidates, cloned in eukaryotic expression vector pCDNA3.1 (referred as p2/4) and tested their ability to elicit protection from T. cruzi infection. In the present study, we subcloned the two antigens in a nanoplasmid that is optimized for delivery, antigen expression, and regulatory compliance standards, and evaluated the nanovaccine (referred as nano2/4) for prophylactic protection against repeat T. cruzi infections. For this, C57BL/6 mice were immunized with two doses of p2/4 or nano2/4 at 21 days interval, challenged with T. cruzi 21 days after 2nd immunization, and euthanized at 10- and 21-days post-infection (pi) corresponding to parasite dissemination and replication phase, respectively. Some mice were re-challenged 21 days pi and monitored at 7 days after re-infection. Without the help of a vaccine, T. cruzi elicited delayed and sub-par T cell activation and low levels of effector molecules that failed to control tissue dissemination and replication of the parasite and provided no protection against repeat challenge infection. The nano2/4 was most effective in eliciting an early activation and production of IFN-γ by CD4+T effector/effector memory (TEM) cells and cytolytic perforin (PFN) and granzyme (GZB) molecules by CD4+ and CD8+ TEM subsets at 10 days pi that was followed by robust expansion of CD4+ and CD8+ TEM and TCM cells with further increase in IFN-γ production at 21 days pi. Consequently, nano2/4-immunized mice exhibited potent control of parasite dissemination at 10 days pi, and tissue parasite burden and tissue inflammatory infiltrate and necrosis were barely detectable at 21 days pi. Furthermore, nano2/4-immunized mice responded to re-challenge infection with high levels of effector molecules production by CD4+ and CD8+ TEM subpopulations that offered even better control of tissue parasite burden than was observed after 1st infection. In comparison, non-vaccinated/infected mice exhibited clinical features of sickness and 59% mortality within 7 days after re-infection. In conclusion, we show that delivery of TcG2 and TcG4 in nanoplasmid offers excellent, protective T cell immunity against repeat T. cruzi infections.